Gender does not impact the short- or long-term outcomes of home-based pulmonary rehabilitation in patients with COPD. Issue 4 (26th October 2020) - Grosbois, Jean-Marie; Gephine, Sarah; Diot, Anne Sophie; Kyheng, Maeva; Machuron, François; Terce, Gaelle; Wallaert, Benoit; Chenivesse, Cécile; Le Rouzic, Olivier
Pulmonary rehabilitation, whether performed at home or in a specialised centre, is effective in the management of COPD. As gender-related differences in COPD were previously reported, we aimed to evaluate the impact of gender on pulmonary rehabilitation outcomes in the short, medium and long term. In this retrospective observational study of 170 women and 310 men with COPD, we compared the outcomes of an 8-week home-based pulmonary rehabilitation programme including an individualised plan of retraining exercises, physical activities, therapeutic education, and psychosocial and self-management support. Exercise tolerance, anxiety, depression, and quality of life (QOL) were assessed using the 6-min stepper test (6MST), Hospital Anxiety and Depression Scale (HADS) and Visual Simplified Respiratory Questionnaire (VSRQ), respectively. Assessments were carried out before, immediately after the pulmonary rehabilitation programme (T2) and at 8 (T8) and 14 months (T14). At baseline, women were younger (mean 62.1 versus 65.3 years), more often nonsmokers (24.7% versus 7.7%) and had a higher body mass index (28 versus 26.4 kg·m −2 ). They more often lived alone (50.6% versus 24.5%) and experienced social deprivation (66.7% versus 56.4%). They had significantly lower exercise tolerance (−34 strokes, 6MST) and higher anxiety and depression (+3.2 HADS total score), but there were no between gender differences in QOL (VSRQ). Both groups showed similar improvements in all outcome measures at T2, T8 and T14 with a tendency for men to lose QOL profits over time. Despite some differences in baseline characteristics, women and men with COPD had similar short-, medium- and long-term benefits of a home-based pulmonary rehabilitation programme. Despite some differences in baseline characteristics, women and men with COPD had similar short-, medium- and long-term benefits of a home-based pulmonary rehabilitation programme https://bit.ly/2XfFakK